Removal of Ni2+ Ion from Artificial Nickel Wastewater by Using Natural Zeolite - KUZUNO, Eiichi; FUJITA, Toyohisa; SHIBAYAMA, Atsushi; MIYAZAKI, Toshio (RESOURCES PROCESSING, 2001)
The Ministry of the Environment of Japan has decided that the content of the nickel (H) ion included in the wastewater should be observed according to the effluent standard. Moreover, the new wastewater treatment techniques for Ni2+ ion are required. On the other hand, zeolite is well known as porous and adsorptive ores. However, most of the zeolite used in practice, as adsorbent, is artificial. As a result, the useful fields of natural and fine zeolite are limited. In this study, the removal of Ni2+ ion from artificial Nickel wastewater was investigated by using no-reforming natural fine zeolite, and ammonium sulfate. It was found that the Ni2+ ion of 50 mg/l in artificial wastewater was completely removed as nickel hydroxide at pH8 employing natural zeorlite 0.5 g and ammonium ion (Al3+ ion) 10 mg/l. In addition, the equilibrium time of removal of Ni2+ ion was shorter. Consequently, it is concluded that in order to removed from waste water as nickel hydroxide the role of no-reforming natural fine zeolite and Al3+ ion were carrier and flocculating aid, respectively.